Legal Protection Of Consumers In Using Cosmetics Containing Hazardous Substances - Dimas Adam Satrio Rachmadhanto; Rika Permatasari; Fhlorida Agustina Simanjuntak (SOUTHEAST ASIA JOURNAL oF GRADUATE OF ISLAMIC BUSINESS AND ECONOMICS, 2025)
The advancement of technology and the growing public demand for appearance have significantly boosted the cosmetic industry's growth. However, this trend is often exploited by irresponsible business actors who manufacture and market cosmetics containing harmful substances, thereby posing serious risks to consumers. This study aims to examine the legal protection for consumers and the responsibility of business actors in the circulation of hazardous cosmetic products. The research method used is normative juridical, focusing on statutory regulations and legal doctrines. The findings reveal that consumer protection is regulated under Law Number 8 of 1999 concerning Consumer Protection, Law Number 36 of 2009 on Health, as well as technical regulations issued by the BPOM and the Ministry of Health. Consumers are entitled to safety and security, while business actors are obligated to ensure product quality and provide compensation for damages caused. This responsibility includes administrative, civil, and criminal aspects, and is upheld even without proven fault (strict liability). Effective law enforcement, government supervision, and increased public legal awareness are essential to achieving optimal consumer protection in the cosmetic industry